دور جودة المعلومات المحاسبية في بناء الاستراتيجية الوطنية للشمول المالي بالمصارف السودانية - عبدالله أبكر, محمد إسحق (جامعة الوادي - University of Eloued, 2022)
Accounting is an open system that operates in an environment that affects it and is affected by it according to the changes and developments that occur and what could affect the accounting work inside or outside the economic units in which it takes place. Among the changes that have occurred at the present time is the emergence of the Corona pandemic and what led with it to the direct impact on human life in general, including on the business sectors in particular, with all its financial activities, which represent the basis of accounting work. The research discussed a main question about how to take advantage of accounting standards in preparing interim financial reports in light of the Corona pandemic, and then clarifying the need for preparing interim financial reports in light of the Corona pandemic based on accounting standards and activating work with them in light of the economic conditions in which economic units operate different. The research has achieved its objectives in clarifying the impact of the Corona pandemic on the accounting work in general and on the output of the accounting work represented by the various financial reports and their timing, as the international accounting standards and financial reporting standards that are required to work were determined in line with the impact of the Corona pandemic on economic units in general and on the accounting work In particular, and then suggesting the nature of accounting work in preparing interim reports in light of the Corona pandemic.
The Role of Quality of Accounting Information in Building the National Strategy for Financial inclusion in Sudanese Banks (Study on a Sample of Banks)
مقال
Keywords: الملائمة ؛ الموثوقية؛ الاستراتيجية الوطنية؛ الشمول المالي.; convenience; reliability; national strategy; Financial Inclusion.